2004
DOI: 10.1017/s1461145704004390
|View full text |Cite
|
Sign up to set email alerts
|

The brain entry of risperidone and 9-hydroxyrisperidone is greatly limited by P-glycoprotein

Abstract: P-glycoprotein (P-gp) in the brain capillary endothelial cell limits the entry of many drugs into the brain. Our previous in-vitro study using ATPase as a marker of P-gp activity suggested that risperidone might be effectively transported by P-gp. In the present study, we compared the concentrations of risperidone and its major pharmacologically active metabolite 9-hydroxyrisperidone (9-OH-risperidone), in plasma, brain and various other tissues between abcb1ab-/- knockout mice which are functionally devoid of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 14 publications
7
90
1
Order By: Relevance
“…Subsequent in vivo studies in P-gp knockout mouse models by our group and others revealed that brain concentration, and ratio of brain-to-plasma concentrations of RSP and its major metabolite, PALI, were significantly higher in knockout mice vs wild-type animals (Wang et al, 2004a;Doran et al, 2005). These results indicated that both RSP and PALI are substrates of P-gp and that their disposition might be influenced by the functional Results are reported as mean7SD, n ¼ 3.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Subsequent in vivo studies in P-gp knockout mouse models by our group and others revealed that brain concentration, and ratio of brain-to-plasma concentrations of RSP and its major metabolite, PALI, were significantly higher in knockout mice vs wild-type animals (Wang et al, 2004a;Doran et al, 2005). These results indicated that both RSP and PALI are substrates of P-gp and that their disposition might be influenced by the functional Results are reported as mean7SD, n ¼ 3.…”
Section: Discussionmentioning
confidence: 93%
“…Our previous work showed that the increase of brain-to-plasma ratio of PALI compared to RSP was greater in P-gp knockout mice than control mice (Wang et al, 2004a). Although both these compounds are P-gp substrates, the added capability of RSP to inhibit P-gp at the level of the BBB suggests a potential for enhancing the entry of PALI into the central nervous system when PALI is formed following the oral administration of RSP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, risperidone was selected as a drug in which net efflux across the BBB was expected. There are several reports based on Mdr1a KO models demonstrating that Pgp reduces risperidone uptake into the brains of both mice (Wang et al, 2004;Doran et al, 2005;Summerfield et al, 2006) and rats (Bundgaard et al, 2012). Using plasma and brain homogenate free fraction analysis, efflux asymmetry was observed in mice (Mau- (Watson et al, 2009).…”
Section: Compartmental Pk Parameter Estimates Based On Simultaneous Fmentioning
confidence: 99%
“…The two mouse genes are supposed to exhibit similar characteristics as the human isoform. Accordingly, the abcb1ab knockout mouse model has been a valuable tool to identify drugs that are P-gp substrates (Doran et al, 2005;Karlsson et al, 2011;Karlsson et al, 2010;Kirschbaum et al, 2008;Uhr et al, 2000;Wang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%